Evaluation of Revised Diagnostic Definition of MS - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Erasmus MC, Rotterdam, The Netherlands, evaluated the 2012 revised IPMSSG consensus definitions in a cohort of children with acquired demyelinating syndromes (ADS) prospectively followed for 2 years from Jan 2007.